الخلفيات الفلسفية والمعرفية لنظريات التفكيك، وأثرها في النقد الأدبي - بوخالفة, فتحي (Université de M'sila, 2014)
يناقش هذا الموضوع بعض ميزات الفكر التفكيكي الحديث، وما أضافه هذا الأخير للنقد الأدبي والفلسفي، والمعرفي بشكل عام. حيث تم التطرق إلى جملة نقاط أساسية تتمثل في: الخاصية المعرفية للكتابة، تعددية الفهم، ثم مدى تواجد هذا النقد الجديد في الكتابة النقدية العربية الحديثة. تمت في البداية معالجة موضوع الخلفيات المعرفية الغربية للفكر التفكيكي الحديث، وذلك من خلال الحديث عن خصوصية الكتابة المعرفية ضمن هذا الفكر، حيث تم التطرق إلى بعض المقولات النقدية الغربية المتعلقة ذا الفكر الجديد، وكيف تصور الغرب منهجية الكتابة ضمنه. أما النقطة الثانية المتعلقة بتعددية الفهم، فتناقش طبيعة الفكر التفكيكي في حد ذاته، كالشك على سبيل المثال، والطبيعة القلقة، وعدم الوقوف عند حدود التفسير الواحد، والفكرة المفردة. وتفسر تعددية الفهم، تعددية القراءة في الفكر النقدي. أما عن وجود التفكيكية في النقد العربي الحديث، فقد تم الوقوف عند ترجمة المصطلح من الثقافة الغربية إلى الثقافة العربية، والتعدد الدلالي الناجم عن هذه الترجمة، ثم الاختلافات الحاصلة نتيجة الترجمات العربية المتعددة. ثم تمت معالجة الفهم المنهجي للفكر العربي الحديث، للنقد التفكيكي. أما النتيجة التي تم التوصل إليها، هي الطبيعة التشكيكية لهذا الفكر الجديد، وكذا عدم الاستقرار على رؤية معينة، إلى جانب الثراء الذي يمكن أن يضيفه للفكر النقدي العربي والعالمي بصفة عامة، نتيجة التساؤلات المستمرة، والحوار المتجدد This topic discusses some of the modern features of the deconstruction thought, and its impacts on the literary, philosophical criticism, as well as its cognitive development in general. It also addresses a number of key points such as: writing knowledge property, pluralistic understanding, and then the presence of such new criticism in modern critical Arabic writing. The issue of background knowledge of Western deconstruction thought has been addressed initially by tackling the particularity of writing knowledge, in which some of the Western critical statements of have been tackled within this cognitive thought, as well as how the West perceives the writing methodology within it. The second point, related to the plurality of understanding, discusses the nature of deconstructive thought itself, such as doubt, the anxious status, and how to go beyond the single interpretation and the individual idea. It also explains the various understanding and the multiple readings in critical thought. As for the presence of deconstruction in the modern Arabic criticism, there has been a stress on the concept while translating from the Western culture to the Arabic one, and the diversity of semantic resulting with the differences occurring as a result of multiple Arabic translations. Then the understandings of the modern systematic Arabic thought and the deconstructive criticism have been treated. The result points at the skepticism in the nature of this new thought, as well as the instability on a certain vision, and how this can enhance to the critical Arabic and the world thought in general, as a result of ongoing questions, and renewed dialogue.
Keywords: Though - deconstruction- critic -culture -ثقافة -فكر-تفكيك- نقد